Estimation of the causes of cracking in the casing of a hot blast duct. (October 2020) - Cherniavsky, A.O.
Highlights: Low-cycle thermal fatigue could appear even at small observed temperature. Closely located cracks are symptom of a thermal fracture but not of mechanical one. High thermal conductivity of a material masks local areas of high thermal gradient. Abstract: The heater of blast furnace intended to provide hot blast and has a metal casing lined inside with refractory bricks. The technological process involves cyclic changes of gas temperature in the heater from 400 to 1200 °C (673 to 1473 K) with cycle duration of 3 h. After some operating time, cracks appear in the casing. Internal pressure in the apparatus is low; nevertheless, the cracks are dangerous because the stream of hot (1200 °C) oxygen-enriched air can damage surrounding structures. A way to prevent cracks depends on the mechanism of their formation. Three possible reasons of the crack formation were considered: uncompensated forces caused by thermal expansion of the entire structure, vibrations, and thermal stresses due local uneven heating of the casing. The observed cracks have different orientations and in some cases are located sufficiently close to each other. This pattern is characteristic for thermal cracks and is not typical for cracks caused by mechanical loads and/or vibrations. Numerical analysis shows that the non-uniformity of temperatures may cause the thermal fatigue cracks despite the fact that the non-uniformity observed on the outer surface of the casing is small enough. Fractographic studies confirmed the thermo-fatigue nature of the cracks. As a possible measure to prevent cracking the usage of 2-layer casing was analyzed, numerical estimations proved potential effectiveness of such solutions.